(untitled) (Acta Polytechnica CTU Proceedings, 2022)
Municipalities are key actors in reaching the sustainable development goals 9, 11, 12, 13 set by the United Nations. The aim of this paper is to develop, on a theoretical level, a sustainable building refurbishment framework for municipalities. The focal point of the framework is reduction of embodied and operational carbon emissions deriving from buildings, including travel-induced emissions. The institutional buildings governed by a Norwegian municipality are the case study objects in this study. The framework that is currently is used in the municipality value the building stock based on the quality and cost of refurbishing them. No framework currently includes travel-induced emissions in the evaluation. The intention is to provide a holistic framework that includes this aspect when deciding if a building should be refurbished or demolished. The omission of transport emissions can lead to truncation errors in assessments. The transport to and from the school generates higher emissions in certain scenarios. Based on the knowledge in the assessment, a theoretical framework that assesses this is developed.